2020
DOI: 10.14689/ejer.2020.88.7
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Understanding Levels of Students with Different Cognitive Styles: An Evaluation in Terms of Different Measurement Techniques

Abstract: This study aimed to determine the conceptual understanding (The Unit of Force) levels of seventh-grade students with different cognitive styles with different measurement techniques and to observe how the conceptual understanding levels measured by different measurement techniques are affected by their cognitive styles. Research Method: The sample of the study, which wasa causal-comparative study, consisted of 80 seventh-grade students in a public school in Ankara. To determine the field-dependent/field-indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Therefore, developing and monitoring conceptual understanding in the science curriculum is one of the main learning outcomes (Aydin et al, 2020). Learning outcomes in the academic field are conceptualized in terms of students' understanding of basic concepts.…”
Section: Indicatorsmentioning
confidence: 99%
“…Therefore, developing and monitoring conceptual understanding in the science curriculum is one of the main learning outcomes (Aydin et al, 2020). Learning outcomes in the academic field are conceptualized in terms of students' understanding of basic concepts.…”
Section: Indicatorsmentioning
confidence: 99%
“…This alternative framework is commonly characterized as a 'theory-like' approach to understanding the world or an alternative mode of cognitive thinking (Bahtaji, 2023;Castro et al, 2020;Mirski et al, 2020). Understanding concepts is very important in the early stages of thinking, especially in the field of physics, which is one of the fields of science that focuses on understanding concepts rather than memory (Ates et al, 2020;Bigozzi et al, 2018;Mason et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the neuroprotective properties of resveratrol and grape phytochemicals has shown that these compounds reduce the toxicity caused by amyloid peptides (Han et al, 2020;Fatemeh et al, 2021), guard against cerebral ischemic injury (Aytac et al, 2022), and protect against kainic acid-induced excitotoxicity (Aytac et al, 2022). The powerful antioxidant activity of RGSE, which in numerous studies has been demonstrated to protect the neural tissue against a range of neurodegenerative disorders brought on by oxidative stress, has been attributed to several neuroprotective qualities of RGSE (Garrab et al, 2019;Aydin and Ates, 2020) The objective of the present investigation was to assess the protective effects of grape seed extract on the cholinergic system in the brain tissue of rats with memory defects.…”
mentioning
confidence: 99%